Peran Penyuluh Pertanian terhadap Keberdayaan Kelompok Tani di Kecamatan Kembaran Kabupaten Banyumas - Wardhana, Zamila Laela Amarthya; Novia, Rifki Andi; Zulkifli, Lutfi (Universitas Galuh, 2026)
The Law No. 19 of 2013 mandates that there should be at least one agricultural extension worker in each village. However, in Kembaran district, one extension worker is responsible for covering three villages, which does not comply with the legal requirements and leads to suboptimal extension activities. The objectives of this research are: (a) To understand the role of agricultural extension worker, the motivation of farmer group members, and the empowerment of farmer groups; (b) To analyze the influence of the role of agricultural extension workers on the empowerment of farmer groups; (c) To analyze the influence of the role of agricultural extension worker on the empowerment of farmer groups through motivation. This research was conducted in Kembaran district, Banyumas Regency. Data collection techniques used cluster sampling with a sample size of 70 respondents, followed by proportional random sampling to determine the sample in each village. The analyses employed in this study include descriptive analysis, Likert scale scoring analysis, and Structural Equation Modeling Partial Least Square (SEM-PLS). The results of this research indicate that the role of agricultural extension workers in the Kembaran district is categorized as effective. The motivation of farmer group members in the Kembaran district is categorized as high. The empowerment of farmer groups in the Kembaran district is categorized as moderately empowered. The role of agricultural extension workers and the empowerment of farmer groups have a direct and significant impact, with a path coefficient of 0.518, a p-value of (0.014<0.05), and a t-statistic of (3.851>1.96). Additionally, the role of agricultural extension workers also influences the empowerment of farmer groups through motivation as a mediating factor, with a path coefficient of 0.331, a t-statistic of (2.455>1.96), and a p-value of (0.014 <0.05).